Administrative process: methodological aspects of legal identification - Karamyshev, Aliaksandr V. (Journal of the Belarusian State University. Law, 2025)
The article examines theoretical and applied issues of administrative process and administrative procedural law in the context of the legislation of the Republic of Belarus and other countries. Their integrative function, including the methodological connection with legal proceedings on administrative (public) disputes is defined. The shortcomings of the linear diversified platform of administrative procedures and proceedings are characterised. The key parameters of systematisation of the administrative process in the form of a sectoral subsidiary model of general and special administrative procedures on the basis of procedural consolidation are designated.
Keywords: administrative process; administrative procedure; administrative procedural law; administrative decision; non-normative legal act; methodological support; consolidation